2008
DOI: 10.1037/0022-006x.76.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Language outcome in autism: Randomized comparison of joint attention and play interventions.

Abstract: This study reports results of a randomized controlled trial aimed at joint attention (JA) and symbolic play (SP) in preschool children with autism, with prediction to language outcome 12 months later. Participants were 58 children (46 boys) with autism between 3 and 4 years of age. Children were randomized to a JA intervention, an SP intervention, or control group. Interventions were conducted 30 min daily for 5-6 weeks. Assessments of JA skills, SP skills, mother-child interactions, and language development w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
366
2
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(398 citation statements)
references
References 38 publications
12
366
2
7
Order By: Relevance
“…Even after controlling for mental age, a significant correlation was found between RJA and IJA skills (on a lower level). However, there are also studies with children with ASD which report nonsignificant correlations between RJA and IJA skills (e.g., Kasari, Paparella, & Freeman, 2008;Murray et al, 2008). The children with ASD in these studies were somewhat older than the children in our study, but the contradictory findings may rather be due to differences in the methods used.…”
Section: Initiation Of Joint Attention Skillscontrasting
confidence: 73%
“…Even after controlling for mental age, a significant correlation was found between RJA and IJA skills (on a lower level). However, there are also studies with children with ASD which report nonsignificant correlations between RJA and IJA skills (e.g., Kasari, Paparella, & Freeman, 2008;Murray et al, 2008). The children with ASD in these studies were somewhat older than the children in our study, but the contradictory findings may rather be due to differences in the methods used.…”
Section: Initiation Of Joint Attention Skillscontrasting
confidence: 73%
“…Given their association with language, one of the most important predictors for the outcome in the long run, stimulating these abilities could also have an effect on language abilities and future development in general. Previous studies indeed showed improvement in language after a training in one of these abilities (Kasari et al, 2008;Paul et al, 2013). Because they all explain unique variance in language, a training programme that focuses on all abilities at once could even be more beneficial, especially in children with limited language abilities.…”
mentioning
confidence: 99%
“…Interventions targeting imitation, joint attention or pretend play have an impact on language ability (e.g. Ingersoll & Lalonde, 2010;Kasari, Paparella, Freeman, & Jahromi, 2008), providing indirect evidence for the link between these skills and language.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre elas destacam-se a atenção conjunta e a imitação que são capacidades essenciais para estabelecer interações sociais e comunicativas para que a linguagem se desenvolva (CHARMAN, 2010;FREEMAN;PAPARELLA, 2006;KASARI et al, 2008). Estudos desenvolvidos por Baron-Cohen (2011 mostram que as crianças com PEA, quando utilizam os gestos de apontar, utilizam primeiro o apontar protoimperativo (ou seja, para pedir) em oposição ao apontar protodelarativo (isto é, para comentar).…”
Section: Desenvolvimento 21 Comunicação Social Na Peaunclassified